Transcriptomic analysis of cyanobacterial alkane overproduction reveals stress-related genes and inhibitors of lipid droplet formation - Arias, Daisy B. (Microb Genom, 2020)
The cyanobacterium Nostoc punctiforme can form lipid droplets (LDs), internal inclusions containing triacylglycerols, carotenoids and alkanes. LDs are enriched for a 17 carbon-long alkane in N. punctiforme , and it has been shown that the overexpression of the aar and ado genes results in increased LD and alkane production. To identify transcriptional adaptations associated with increased alkane production, we performed comparative transcriptomic analysis of an alkane overproduction strain. RNA-seq data identified a large number of highly upregulated genes in the overproduction strain, including genes potentially involved in rRNA processing, mycosporine-glycine production and synthesis of non-ribosomal peptides, including nostopeptolide A. Other genes encoding helical carotenoid proteins, stress-induced proteins and those for microviridin synthesis were also upregulated. Construction of N. punctiforme strains with several upregulated genes or operons on multi-copy plasmids resulted in reduced alkane accumulation, indicating possible negative regulators of alkane production. A strain containing four genes for microviridin biosynthesis completely lost the ability to synthesize LDs. This strain exhibited wild-type growth and lag phase recovery under standard conditions, and slightly faster growth under high light. The transcriptional changes associated with increased alkane production identified in this work will provide the basis for future experiments designed to use cyanobacteria as a production platform for biofuel or high-value hydrophobic products.